Therapeutic follow-up in hospitalization: social inclusion, recovery of citizenship and respect for individuality - Regina Célia Fiorati; Toyoko Saek; Arlete Soares Belluzzo; Arlete Soares Belluzzo; Philip Sidney Pacheco Badiz (Faculdade de Medicina de Botucatu (Unesp), 2008)
This study was carried out in a psychiatric crisis hospitalization unit, with the aim of drawing up a proposal for implementing therapeutic follow-up as part of the therapeutic program at this unit. The concept of therapeutic follow-up was envisaged as an important resource to be included in psychosocial rehabilitation projects, with the following goals: linking users with extra-hospital services, avoiding re-hospitalization and achieving inclusion in social networks. The study consisted of an exploratory-descriptive case study with a qualitative approach to data. Participant observation and a field diary were the techniques used for gathering and recording data. The difficulties experienced were correlated with the spheres of social networks, family, institutional relationships and society. The results included heeding the patient's and the family's suffering and including users in social networks, extra-hospital services and community organizations.